ANALISIS PENGARUH EFEKTIFITAS DEWAN KOMISARIS DAN KOMITE AUDIT TERHADAP KUALITAS SUSTAINABILITY REPORT - Esther Monica Setiawan; Petrus Ridaryanto (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2022)
This study examine the effect of Board of Commissioner’s Effectiveness, as measured by ther size, gender diversity and board of commissioners’s education and the Audit Committee’s Effectiveness as measured by size, number of meetings, and the audit committes’s accounting education onthe quality of sustainability report. This study uses the secondary data from mining companies from 2015 to 2019 from IDX. The sample selection method used is purposive sampling, obtained 12 companies with total of 43 sample. The analytical method used is multiple regression analysis with SPSS 26. The results showed that the size of board of commissioners, the gender diversity of the board of the commissioners, the education of the board of the commissioners, the size of the audit committee had no effect on the audit quality of the sustainability report so that all of the hypotheses that had been made were rejected.